2015
DOI: 10.1177/1535370214566558
|View full text |Cite
|
Sign up to set email alerts
|

Versatile communication strategies among tandem WW domain repeats

Abstract: Interactions mediated by short linear motifs in proteins play major roles in regulation of cellular homeostasis since their transient nature allows for easy modulation. We are still far from a full understanding and appreciation of the complex regulation patterns that can be, and are, achieved by this type of interaction. The fact that many linear-motif-binding domains occur in tandem repeats in proteins indicates that their mutual communication is used extensively to obtain complex integration of information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Although information on the binding specificities of individual domains may be available, it does not necessary reflect the specificity of the domains in the context of the full-length proteins. In addition, connected domains of a bait protein might bind to linked motifs in a target protein, which may increase the apparent affinity and enhance the specificity of the interactions [ 91 , 92 ]. Thus, dedicated approaches should be developed to account for such scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Although information on the binding specificities of individual domains may be available, it does not necessary reflect the specificity of the domains in the context of the full-length proteins. In addition, connected domains of a bait protein might bind to linked motifs in a target protein, which may increase the apparent affinity and enhance the specificity of the interactions [ 91 , 92 ]. Thus, dedicated approaches should be developed to account for such scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, structural studies suggested that intermolecular interactions outside of core binding WW motifs could also affect their ability to bind to a particular partner [26]. Furthermore, as all mammalian NEDD4 E3s have tandem repeats of more than one WW domain, the WW domain-ligand interactions can be further fine-tuned by the versatile cooperativity among these tandem repeats [25].…”
Section: Nedd4 Family Membersmentioning
confidence: 99%
“…The WW domains of NEDD4 E3s are believed to be the main mediators of their interactions with substrates and adaptors, primarily through association with PY motifs (PPxY or LPxY, x is any amino acid residue) on their interacting partners. In addition, WW domains have been shown to interact with phosphoserine or phosphothreonine residues, as well as with several non-canonical regions [25].…”
Section: Nedd4 Family Membersmentioning
confidence: 99%
“…The fact that the members of the NEDD4 family harbor multiple WW domains raises the possibility that tandem WW domain repeats may cooperate to enhance specificity and binding affinity [116]. For instance, the binding of the NEDD4 family member NEDD4-2 to its target SMAD2/3 first involves the phosphorylation-dependent binding of its WW3 domain to a site downstream of a PY motif, which positions the WW2 domain so that it can bind the PY motif, ultimately enhancing the total binding affinity [117].…”
Section: Regulation Of Cx43 Gap Junctions By Nedd4mentioning
confidence: 99%